A Novel Four-Phase Active Boost Switched Reluctance Inverter for High Speed SRM Drive - J. L. Beniwal; R. K. Tripathi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
A novel four-phase active boost switched reluctance inverter (SRI) having capability of improving performance of high speed SRM drive is presented. The proposed SRI provides fast fluxing as well as rapid de-fluxing with only two additional small voltage rating boost capacitors as compared to conventional SRI. Two boost capacitors were connected in such a way that each boost capacitor handles two alternate phases. This is an alternate solution to the problem caused by the overlap phase current which prevents the boost capacitor voltage to buildup. In proposed SRI, either of a boost capacitor and dc-link source forms the series connection during fluxing and de-fluxing period. Thus, the higher voltage for fluxing of SRM and negative higher voltage for de-fluxing of SRM are obtained. The operating mode analysis of proposed SRI are given in detail. The simulation for the conventional and proposed SRI has been performed and compared. And results justify the superior performance of proposed SRI.